Sistem Informasi Persediaan Obat di Puskesmas Sepatan Tangerang - Amerta, Yusuf; Ziveria, Mira (KALBISCIENTIA Jurnal Sains dan Teknologi, 2020)
Sepatan Health Center is a facility or health service agency that serves for the health of thecommunity on district Sepatan, at this place there is a pharmacy which is a container medicine. As afunction of accelerating and facilitate the activities of drug data management, it needs technology thatis implemented in the health service agency that is Sepatan Tangerang Health Center. The purpose ofthis research is to build the Information System of Drug Inventory at Sepatan Tangerang Public HealthCenter with web based by using Prototype development method which starts with flowchart analysis,design using UML Diagram and PHP programming language and MySQL database and test with BlackBox. The result of this research is a Drug Inventory Information System that can perform the process ofdrug data input transactions, receipt transactions, location change transactions, expense transactionsand booking transactions and generate a good report of each transaction made.